PENINGKATAN KEMAMPUAN MENGHAFAL MUFRADAT SISWA KELAS VII SMP NURUL HUDA MENEMENG: IMPROVING OF MUFRADAT MEMORIZE SKILL AT SEVENTH CLASS STUDENTS OF SMP NURUL HUDA MENEMENG - Mohammad Zaki; Rahmat Linur (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2022)
This research explain the personality of students were still unable to pronounce and write correctly, it is difficult to understand the meaning of Arabic words both in oral communication and written communication such as understanding reading texts. In addition, they are still not able to use Arabic vocabulary in the context of the right sentence. Therefore, this study aims to provide one method that can be applied in learning Arabic vocabulary is the singing method. This research uses a qualitative research method, which was carried out in seventh grade students of SMP Nurul Huda in Menemeng as the object of research, and the subject the research is the researcher himself who is also the data collector. The data collection techniques in the form of interviews, questionnaires, field data, documents, notes, and other notes. From the results of this study indicate that the use of the singing method to improve the ability of memorize Arabic mufrodat for students of Class VII SMP Nurul Huda Menemeng is effective, as well as the teacher tries harder to be able to mastering the students with the good atmosphere of class, so that all students can catch more lessons and memorization, without any coercion and without any sense of pressure in memorizing of vocabulary. Keywords: memorize, vocabulary, improve Abstrak: Penelitian ini berangkat dari kepribadian dimana banyaknya siswa yang masih belum mampu mengucapkan dan menuliskan dengan benar, sulit memahami makna kata bahasa Arab baik dalam komunikasi lisan maupun dalam komunikasi tertulis seperti memahami teks bacaan. Selain itu mereka masih belum mampu menggunakan kosa kata bahasa Arab dalam konteks kalimat yang tepat. Oleh karena itu penelitian ini bertujuan memberikan salah satu metode yang dapat diterapkan dalam pembelajaran kosa kata Bahasa Arab, yaitu metode bernyanyi. Penelitian ini menggunakan metode jenis penelitian kualitatif, yang dilakukan pada siswa kelas VII SMP Nurul Huda di Menemeng sebagai objek penelitian, dan yang menjadi subjek penelitiannya adalah peneliti sendiri yang sekaligus sebagai pengumpul data. Adapun teknik pengumpulan data berupa wawancara, angket, data lapangan, dokumen, nota, dan catatan lain. Dari hasil penelitian ini menunjukkan bahwa penggunaan metode bernyanyi untuk meningkatkan kemampuan menghafal mufrodat Bahasa Arab bagi siswa dan siswi Kelas VII SMP Nurul Huda Menemeng efektif, begitu jga dengan guru berupaya lebih keras untuk bisa menguasai siswa dan suasana kelas dengan baik, agar semua siswa bisa menangkap pelajaran maupun hafalan lebih banyak,tanpa ada paksaan dan tanmpa ada rasa tekanan dalam menghafal mufrodat. Kata Kunci: menghafal, mufradat, peningkatan